Human and Artificial Intelligence Interaction from the Perspective of Social Construction of Technology - Elmaresa, Maria Vina; Irwansyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This research examines the socio-cultural impacts on the adoption and perception of artificial intelligence, focusing on its role as a communicator in direct human-machine interactions within the framework of Human-Machine Communication. As artificial intelligence becomes increasingly woven into daily human experiences, individuals are turning to it for emotional support and companionship, as seen in narratives of emotional relationships with generative AI. The research aims to understand how direct interactions with artificial intelligence influence perceptions of its utility and emotional closeness, contrasting these with indirect interactions. Employing a qualitative approach, the researchers conducted in-depth interviews, which reveal that initial skepticism about artificial intelligence diminishes with increased usage. Informants start recognizing artificial intelligence not just as a tool but as a companion providing non-judgmental support, facilitated by artificial intelligence-mediated communication. Findings suggest a significant perceptual shift among users, viewing artificial intelligence as capable of fulfilling emotional roles in human relationships. This research contributes to Human- Machine Communication by highlighting the qualitative nuances in how artificial intelligence is embedded in daily life, affecting social and emotional interactions. The research underscores artificial intelligence's potential not only in enhancing productivity but also in serving as a meaningful social and emotional partner. The Social Construction of Technology framework is used to analyze how different social groups influence the development of artificial intelligence, illustrating that the evolution of technology is shaped by societal interactions and perceptions.